Qualitative research and evaluation methods - Patton, Michael Quinn (Sage Publications, 2002)
The book that has been a resource and training tool for countless applied researchers, evaluators, and graduate students has been completely revised with hundreds of new examples and stories illuminating all aspects of qualitative inquiry. Patton has created the most comprehensive, systematic, and up-to-date review of qualitative methods available.